Unemployment in the United States After Traumatic Brain Injury for Working-Age Individuals. Issue 3 (May 2015) - Cuthbert, Jeffrey P.; Harrison-Felix, Cynthia; Corrigan, John D.; Bell, Jeneita M.; Haarbauer-Krupa, Juliet K.; Miller, A. Cate; Bell, Jeneita M.; Taylor, Christopher A.; Breiding, Matthew J.
<x xml:space="preserve">Abstract</x> Objective: To estimate the prevalence of unemployment and part-time employment in the United States for working-age individuals completing rehabilitation for a primary diagnosis of traumatic brain injury (TBI) between 2001 and 2010. Design: Secondary data analysis. Setting: Acute inpatient rehabilitation facilities. Participants: Patients aged 16 to 60 years at injury who completed inpatient rehabilitation for TBI between 2001 and 2010. Main Outcome Measures: Unemployment; Part-time employment. Results: The prevalence of unemployment for persons in the selected cohort was 60.4% at 2-year postinjury. Prevalence of unemployment at 2-year postinjury was significantly associated with the majority of categories of age group, race, gender, marital status, primary inpatient rehabilitation payment source, education, preinjury vocational status, length of stay, and Disability Rating Scale. The direction of association for the majority of these variables complement previous research in this area, with only Hispanic ethnicity and the FIM Cognitive subscale demonstrating disparate findings. For those employed at 2-year postinjury, the prevalence of part-time employment was 35.0%. The model of prevalence for part-time employment at 2-year postinjury was less robust, with significant relationships with some categorical components of age group, gender, marital status, primary payment source, preinjury vocational status, and Disability Rating Scale. Conclusions: The prevalence of unemployment for patients completing inpatient rehabilitation for TBI was substantial (60.4%). The majority of factors found to associate with 2 years' unemployment were complementary of previously published research; however, these were often smaller in magnitude than previous reports. The prevalence of part-time employment was also an issue for this cohort and included 35.0% of all employed individuals. In regard to the determination of factors associated with part-time employment, additional analyses that include more fine-grained factors associated with employment, including physical and psychosocial functioning, are recommended.